A micromechanical Sliding-Damage Model Under Dynamic Compressive Loading - Ahmadi, Mohammad Hossein; Molladavoodi, Hamed (Periodica Polytechnica Civil Engineering, 2019)
For most rock materials, there exists a strong coupling between plastic flow caused by sliding along micro-crack faces and damage evolution due to nucleation and growth of wing-cracks. The aim of this article is to develop the self-consistent based micromechanical model by taking into account the coupling between frictional sliding and damage process under dynamic compressive loading. The developed model algorithm was programmed in the commercial finite difference software environment for numerical simulation of rock material to investigate the relationship between the mechanical behaviour and microstructure. Eventually while the stress intensity factor at flaw tips exceeds the material fracture toughness, the wing-cracks are sprouted and damage evolution occurs. For frictional closed cracks, an appropriate criterion for the onset of frictional sliding along micro-cracks was proposed in this paper. Also, plastic strain increments were determined by the flow rule, consistency condition and normality rule within the thermodynamic framework. The simulation results demonstrate that the developed micromechanical model can adequately reproduce many features of the rock behaviour such as hardening prior to the peak strength, softening in post-peak region, damage induced by wing-cracks and irreversible deformations caused by frictional sliding along micro-cracks. Furthermore, the softening behaviour of material in post-peak region is affected and the material undergoes higher values of strains and damage up to the residual strength. Therefore, the rock sample simulation with the coupled frictional sliding-damage model could increase plasticity and ductility of the rock in post-peak region because of regarding plastic strains caused by the frictional sliding along micro-cracks.